Ruci's Joint Marketing Public Relations Strategy in Conducting and Communicating Rebranding to Increase Sales Value - Theresia Sharron Sanjaya (Syntax Corporation Indonesia, 2021)
This research is expected to provide clearer explanations to readers regarding the Strategy of Marketing Public Relations Ruci’s Joint conducting and communicating rebranding to increase sales value. The purpose of this research is to know Marketing Public Relations Ruci’s Joint’s Strategy in conducting and communicationg rebranding to increase sales value. The main theory used is Marketing Public Relations and the other supporting theories are brand, and rebranding. The method of insulation used is a qualitative descriptive method. Data collection thechniques are done by conducting in-depth interviews, and observations. The speakers in this study are form internal and external companies. The data obtained from the subject of this study are analyzed by data analysis techniques, while for the data trust techniques using source triangulation data.